Estudo das subpopulações de linfócitos, células natural killer, células dendríticas e monócitos em sangue de cordão umbilical e placentário - Barbosa, Miriam Cristina Rodrigues [UNIFESP] (2017)
Introduction: The treatment of food allergy (AA) consists on total dietary exclusion of foods that contain the allergens to which the patient is sensitized. Fear of accidental ingestion and occurrence of adverse reactions negatively affects health-related quality of life (HRQoL) of patients and their family members. The identification of the main factors capable of impacting the HRQL of this population can help in choosing the best ways to approach the diagnosis and to direct the treatment of this disease. Objective: To translate into Portuguese and culturally adapt to Brazil two questionnaires that estimate the HRQoL of children with AA and their parents and evaluate their psychometric properties. To identify the association between the HRQoL scores and the clinical and socioeconomic data of the studied population. Method: The translation and cultural adaptation were performed according to the method proposed by the World Health Organization. After this step, the Brazilian version of the specific questionnaire to assess the quality of life of children with AA was answered by 183 parents already the specific questionnaire to evaluate the quality of life of the parents of these children was answered by 148 participants. The internal consistency was evaluated by the Cronbach's alpha coefficient, the intraclass correlation coefficient between the test and retest of the questionnaires applied at an interval of 7 to 30 days and for the evaluation of the construct, the Correlation coefficient of Spearman. The scores obtained with the application of the Brazilian versions of the specific questionnaires to evaluate the quality of life related to AA were compared to the scores obtained with the application of generic questionnaires that evaluate the HRQoL of children and their parents, considering the care they should have with their health (PedsQL). Finally, the means of the scores obtained with the specific questionnaires for AA were compared with the clinical and socioeconomic characteristics of the studied population, using the Analysis of Variance. Results: The mean scores obtained on the HRQoL of children and their parents were 1.44 and 3.35, respectively. The -Cronbach Coefficients were 0.85 and 0.91, respectively, which demonstrated good internal consistency of the instruments. The intraclass correlation coefficients between the tests and the retests were 0.874 and 0.836, respectively, showing good reproducibility for both questionnaires; and the correlation between the specific and generic questionnaires was significant (-0.27 for the children, -0.64 for the parents, p <0.05). The scores obtained from interviews with the mothers were significantly lower than those of the parents. The higher the child's age, the worse the scores obtained. History of anaphylaxis, increased number of foods which triggered symptoms of AA and increased number of systems involved in the reactions, were associated with a greater negative impact on HRQoL. Conclusion: The specific questionnaires to evaluate the quality of life of children under 4 years of age allergic to food and of their parents were satisfactorily translated into Portuguese, culturally adapted and validated for use in Brazil. HRQL is negatively influenced by the greater severity of the disease, the greater number of food involved and the greater age of the child. Mothers have worse quality of life scores compared to their parents.